Using programmable calculators for financial applications. (4th August 2014) - Sarkar, Salil K.
Electronic calculators are becoming an indispensable tool for financial practitioners. Several text books recommend the use of calculators in finance classes. However, the variety of forms and sizes make it a problem to pick the right one. Some recent articles have discussed the use of financial calculators and others have attempted to program the Black–Scholes option pricing model in a programmable calculator using 'Reverse Polish Notation' (RPN) logic. Thus a practitioner may be required to carry several calculators, for the different types of application in his day–to–day job. Alternatively, he may carry a laptop computer with a number of programs. However, a lot of times it may be more convenient and highly economical to have a pocket calculator that can serve equally well. This article selects a series of economical programmable calculators using algebraic logic, and programs the time value functions as well as the Black–Scholes option pricing model in the same calculator. It gives the complete programming steps, including a brief theoretical background. Subsequently, it gives an application section in which it takes the reader step by step through the various programs showing the display of the calculator at every step. Thus the reader can check the programming steps and debug for errors if the answers do not match.